2009
DOI: 10.1111/j.1750-3841.2008.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dextrose Equivalent Value and Number Average Molecular Weight of Maltodextrin by Osmometry

Abstract: Dextrose equivalent (DE) value is the most common parameter used to characterize the molecular weight of maltodextrins. Its theoretical value is inversely proportional to number average molecular weight (M n ), providing a theoretical basis for correlations with physical properties important to food manufacturing, such as: hygroscopicity, the glass transition temperature, and colligative properties. The use of freezing point osmometry to measure DE and M n was assessed. Measurements were made on a homologous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 7 publications
0
19
0
2
Order By: Relevance
“…34 As evident from Table I, higher the percentage grafting, higher is the number-average molecular weight. This is due to the greater number of acrylamide monomers grafted.…”
Section: Characterizationmentioning
confidence: 92%
“…34 As evident from Table I, higher the percentage grafting, higher is the number-average molecular weight. This is due to the greater number of acrylamide monomers grafted.…”
Section: Characterizationmentioning
confidence: 92%
“…The DE was also quantified as this value is a measure of the amount of starch molecules, because each starch molecule carries one reducing end. As such, the DE gives the Mn of the products obtained after hydrolysis of the RSs . It showed that WFR had the highest DE (8.1 g per 100 g), whereas JD and dEtenia were intermediate (respectively, 4.2 g per 100 g and 4.4 g per 100 g), and AmyloseV had the lowest DE (1.2 g per 100 g) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…With increasing maltodextrin concentration, the osmolarity of the solution increases54. At relatively high osmolarities, however, adaptive responses to osmotic stress will limit the rate of H 2 O 2 entry into a cell55.…”
Section: Discussionmentioning
confidence: 99%